Glial but not neuronal development in the cochleo-vestibular ganglion requires Sox10. - Stolt, Claus; Wegner, Michael; et al. (Journal of Neurochemistry, 2010)
The cochleo-vestibular ganglion contains neural crest-derived glial cells and sensory neurons that are derived from the neurogenic otic placode. Little is known about the molecular mechanisms that regulate the tightly orchestrated development of this structure. Here, we report that Sox10, a high-mobility group DNA-binding domain transcription factor that is required for the proper development of neural crest cell derivatives, is specifically expressed in post-migratory neural crest cells in the cochleo-vestibular ganglion. Using Sox10-deficient mice, we demonstrate that this transcription factor is essential for the survival, but not the generation, of the post-migratory neural crest cells within the inner ear. In the absence of these neural crest-derived cells, we have investigated the survival of the otocyst-derived auditory neurons. Surprisingly, auditory neuron differentiation, sensory target innervation and survival are conserved despite the absence of glial cells. Moreover, brain-derived neurotrophic factor expression is increased in the hair cells of Sox10-deficient mice, a compensatory mechanism that may prevent spiral ganglion neuronal cell death. Taken together, these data suggest that in the absence of neural crest-derived glial cells, an increase trophic support from hair cells promotes the survival of spiral ganglion neurons in Sox10 mutant mice. © 2010 International Society for Neurochemistry.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.glialb
Keywords: auditory neurons; development; glial cells; inner ear; neural crest cells; Sox genes